Platelet-rich plasma as an Alternative Supplement for Enhancing CD Marker Expression in Umbilical Cord-Derived Mesenchymal Stem Cells - Prianggodo, Putra Agung; Septiana, Wahyunia Likhayati; Junaidi, Helsy; Astuti, Sastia Winda (Biology, Medicine, & Natural Product Chemistry, 2025)
This study aimed to assess the effectiveness of platelet-rich plasma (PRP) and fetal bovine serum (FBS) as culture supplements for mesenchymal stem cells (MSCs) isolated from umbilical cord tissue. The study focused on the efficiency of xeno-free PRP in enhancing cell adhesion and proliferation and looked at cell surface markers for MSC characterization. Until the cells achieved 80% confluency, three repeats of FBS and PRP were added to the culture medium of mesenchymal stem cells derived from umbilical cord tissue in passage 10. Following harvesting, an assay kit for human mesenchymal stem cells was used to color the cells. Using flow cytometry, the surface markers CD73, CD90, CD105, and the negative marker CD44 were evaluated in the samples. Cells supplemented with PRP expressed more positive indicators and fewer negative markers. Whereas the results for CD90, CD105, and the negative marker were insignificant, the expression of CD73 increased significantly. PRP can enhance CD marker expression by acting as a substitute for FBS in the culture of xeno-free umbilical cord-derived MSCs.